QOLP-20. QUALITY OF LIFE IN THE PHASE III CeTeG/NOA-09 TRIAL RANDOMIZING CCNU/TEMOZOLOMIDE (TMZ) COMBINATION THERAPY VS. STANDARD TMZ THERAPY FOR NEWLY DIAGNOSED MGMT-METHYLATED GLIOBLASTOMA. (5th November 2018) - Weller, Johannes; Tzaridis, Theophilos; Steinbach, Joachim; Schlegel, Uwe; Hau, Peter; Krex, Dietmar; Grauer, Oliver; Goldbrunner, Roland; Bähr, Oliver; Uhl, Martin; Seidel, Clemens; Tabatabai, Ghazaleh; et al.
Abstract: The CeTeG/NOA-09 trial demonstrated a significant survival benefit of radiotherapy with CCNU/temozolomide (TMZ) combination therapy compared to standard TMZ therapy as first-line treatment of O6-methylguanine-DNA methyltransferase (MGMT)-promotor hypermethylated glioblastoma. Quality of life (QoL) assessment was a secondary objective to investigate if CCNU/TMZ combination chemotherapy has a detrimental effect on patient's QoL. PATIENTS AND METHODS: Patients (n=141) received standard radiotherapy and were randomized (1:1) for CCNU/TMZ or standard TMZ. The modified intention-to-treat population consisting of 129 patients was analyzed. At least every three months, Karnofsky performance score (KPS) was determined and QoL was measured using the EORTC-QLQ C30 and BN20 questionnaires. A longitudinal mixed-model analysis was used to evaluate differences between treatment arms in the course of KPS and QoL over time. Time to first deterioration was analyzed using a Cox regression model. RESULTS: Over a period of four years, longitudinal mixed-model analysis detected no significant impairment of QoL or KPS in the CCNU/TMZ arm as compared to the TMZ arm. Time to deterioration was prolonged in one QoL domain, motor dysfunction, for patients in the experimental arm. CONCLUSION: Intensified alkylating chemotherapy with CCNU/TMZ for patients with MGMT promotor-methylated glioblastoma did not lead to a reduction of QoL or KPS compared to TMZ standard therapy.